Tax Planning Strategies for High-net-worth Individuals and Businesses: Minimizing Tax Liabilities Within Legal Frameworks - Junaidi, Junaidi (Penelitian dan Pengembangan Ilmu, 2024)
Tax planning is an important element for high net worth individuals and companies in minimizing tax liabilities within legal limits. This research aims to explore tax planning strategies used in various countries with different tax systems, as well as their impact on compliance and optimizing the tax burden. Using a systematic literature review method with the PRISMA framework, this research analyzes articles from reputable international journals to evaluate different tax planning approaches. The research results show significant variations in tax planning strategies, which are influenced by differences in international tax regulations and the unique conditions of each country. The implications of this research emphasize the importance of adapting tax planning strategies to the legal framework to ensure tax compliance and optimization, as well as the need for more inclusive and effective tax policies.